Status of Helicobacter pylori Eradication in Japan - Gwang Ha Kim (Yong Chan Lee, 2017)
Like Korea, Japan is one of the countries with the highest incidence of gastric cancer and Helicobacter pylori infection. However, the guidelines on H. pylori eradication differ between Japan and Korea. Since 2013, the indications for H. pylori eradication in Japan include all H. pylori-associated gastritis for prevention of gastric cancer and H. pylori dissemination. For first-line therapy, a standard triple therapy comprising of amoxicillin, clarithromycin, and a proton pump inhibitor is used for 1 week. However, the eradication rate has recently decreased owing to the increasing resistance of H. pylori to clarithromycin. For second-line therapy, a combination of amoxicillin, metronidazole, and a proton pump inhibitor is used for 1 week, but the eradication rate is still unacceptable (≒90%). The main distinguishing aspects of eradication therapy in Japan are the low dose of antibiotics (especially clarithromycin), the short duration (7 days), the low resistance rate of H. pylori to metronidazole, the absence of a bismuth-based regimen, and the recent approval of potassium ion-competitive acid blocker for eradication therapy.